Transvenous proximal closure of large congenital coronary arteriovenous fistula using the single Amplatzer vascular plug in a 3-year-old girl - Hae In Jang; Young Earl Choi; Hwa Jin Cho; Young Kuk Cho; Jae Sook Ma (Korean Pediatric Society, 2013)
Congenital coronary arteriovenous fistulas (CCAFs) are rare coronary artery abnormalities in which blood is shunted into a cardiac chamber or great vessel. If the fistula itself is large and tortuous, it is generally recommended to occlude the fistula to prevent several complications. In approaches of transcatheter occlusion, the transvenous approach is preferred over the transarterial approach. The transvenous approach would enable the cannulation of a relatively larger catheter or sheath without potential damage to the femoral vessels or normal coronary arteries, which can occur in the transarterial approach. The transvenous approach may also minimize the blind pouch after releasing the devices. Herein, we report the success of transvenous proximal closure of a CCAF using an Amplatzer vascular plug (AVP) in a 3-year-old patient with cardiomegaly. Complete occlusion was achieved by a single AVP and thrombus formation of the distal aneurysmal portion of the fistula. We suggest that this strategy of closing the proximal end with a dilated fistula using a single AVP by the transvenous approach may be a good option in treating CCAFs in a young child.